Peranan Bank Sumut KCP Hamparan Perak Terhadap Perkembangan Usaha Mikro - Haddad Aidil Nafis; Muhammad Lathief Ilhamy Nasution (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The aim of this research is to determine the role of the North Sumatra Sharia Bank in the growth of micro, small and medium enterprises at the North Sumatra Bank KCP Pelayan Perak and identify obstacles in the development of MSMEs. This research uses qualitative field research techniques which focus more on the details of an in-depth knowledge problem. In its simplest form, field research is an investigation of data collected from a research location or field with the aim of collecting data or information, such as books, notes, papers and other references about MSMEs. Bank Sumut KCP Hamparan Perak is where this data was found. The findings of this research include the role of Bank Sumut KCP Hamparan Perak in maximizing MSMEs consisting of three things, namely providing MSME financing products in the form of Sumut Sejahtera, monitoring how customers' businesses are financed and developed, and providing capital for MSMEs in the form of management advice and business supervision to clients. With this research, it is hoped that Bank Sumut KCP Hamparan Perak can improve its operations, make its employees more comfortable in serving the community, and create a customer-friendly environment.